What Can the Organization of the Brain’s Default Mode Network Tell us About Self-Knowledge? - Moran, Joseph M.; Kelley, William M.; Heatherton, Todd F. (Frontiers in Human Neuroscience, 2013)
Understanding ourselves has been a fundamental topic for psychologists and philosophers alike. In this paper we review the evidence linking specific brain structures to self-reflection. The brain regions most associated with self-reflection are the posterior cingulate [pCC] and medial prefrontal [mPFC] cortices, together known as the cortical midline structures. We review evidence arguing that self-reflection is special in memory, while noting that these brain regions are often engaged when we think about others in our social worlds. Based on the cortical midline structures’ patterns of connectivity and activity, we speculate about three possible interpretations of their role in supporting self-reflection that are somewhat overlapping, and not intended to be mutually exclusive. First, self may be a powerful, but ordinary case for a cognitive system specialized for thinking about people. Second, mPFC may serve as a processing ‘hub’, binding together information from all sensory modalities with internally-generated information. Third, mPFC may serve as a cortical director of thought, helping to guide moment-by-moment conscious processing. Suggestions are made for future research avenues aimed at testing such possibilities.